Development of an experimental apparatus aimed at performing thermal-induced spalling tests based on a propane gas burner through tests on ultra-high performance concrete. (30th June 2020) - Ouedraogo, E.; Djaknoun, S.; Uch, B.; Nguyen, Q.T.; Missemer, L.; Miras, A.; Malecot, Y.
Highlights: Effective for studying the conditions in which spalling of concrete occurs. Heating conditions close to those of ISO 834 standard fire are applicable. Measured specimen surface temperature differs from the temperature of the furnace. Indicative statistics on the characterization of debris ejected during spalling of concrete. Useful results for calibrating concrete damage models in TM or THM approach. Abstract: The modelling of thermal spalling of concrete structures is a challenging subject that requires relevant and reliable experimental data concerning temperature distribution and material degradations. For this purpose, a new device dedicated to the study of concrete thermal-induced spalling was designed and manufactured and is now under development. The experimental apparatus consists of a propane supplied burner surmounted by a furnace that can heat uniformly a concrete specimen surface according to ISO 834 standard fire curve. Temperature-time curves on the heated face and at different points of high performance concrete specimens that underwent spalling are reported and commented. The thermal conditions for which spalling and explosive spalling occurred are also examined and analyzed. An indicative thermal gradient value of about 14 °C/mm was found to be critical for the spalling occurrence. The analysis of the debris mass and dimensions distributions highlighted their usefulness in numerical modelling purpose. Lastly, the paper analyses how the undertaken tests results can ease the finite element modelling of spalling of concrete structures.